JURIDICAL ANALYSIS OF THE COLLABORATION BETWEEN IMMIGRATION AND STAKEHOLDERS AT BATAM CENTRE INTERNATIONAL PORT IN EFFORTS TO PREVENT HUMAN TRAFFICKING CRIMES (RESEARCH STUDY IN BATAM CITY) - Fajar Ramadani; Soerya Respationo; Siti Nurkhotijah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The Criminal Act of Human Trafficking (TPPO) is a transnational crime that has a serious impact on human rights, especially in border areas such as Batam City, which has direct access to neighboring countries through the Batam Centre International Port. Preventing TPPO requires effective collaboration between Immigration and various stakeholders such as the Police, port authorities, and civil society organizations. This study aims to analyze the legal regulations, implementation, obstacles, and solutions regarding the collaboration between Immigration and stakeholders in efforts to prevent TIP at Batam Centre International Port. The methods used are normative juridical and empirical juridical legal research methods with a statutory approach and a sociological approach. Data was obtained through document studies and direct interviews with Immigration, the Police, KSOP, and NGOs. The analysis was carried out using three main theories: Max Weber's Theory of Authority, Lawrence M. Friedman's Legal System Theory, and Soerjono Soekanto's Theory of Legal Effectiveness. The results of the study show that although the legal framework for collaboration has been regulated through Law Number 6 of 2011 and Law Number 21 of 2007, as well as several technical memorandums of understanding, its implementation is still not optimal. The identified obstacles include overlapping authorities, the absence of inter-agency SOPs, limited resources, and a weak culture of cooperation. Current collaboration remains sectoral and has not been institutionalized on a permanent basis. This study recommends the establishment of integrated inter-agency SOPs, the creation of permanent coordination posts at ports, and collaborative training and incentive systems to strengthen institutional synergy in the prevention of human trafficking in border areas.